Contents and Language of Songs about Thailand’s 2011 Floods: A Reflection of Thai Society - Koohacharoen, Tuangrat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
The objective of this paper is to study the contents and the language use in songs reflecting Thai society. The paper focuses on presentation of emotions and feelings of Thai people towards Thailand’s floods through content analysis of the lyrics of 50 songs released from October to December 2011. The contents found mostly encouraged victims, followed by Thai flood incidents and campaigns asking Thais to help each other. The reflections found were mostly their living and sufferings, followed by the generosity of Thai people. As for the language use, the titles of most songs were direct to the point and stimulating. The songs’ lyrics were outstanding in terms of word selection and meaning levels. Vowel and consonant rhymes, diverse intonation and compounds are used at the word selection level. As for the meaning level, word and meaning repetition and figures of speech are used. Incidents of Thai floods and the help for victims are portrayed in the music videos of the songs. Their lyrics were beautiful in terms of both sound and meanings. They could convey the incidents of 2011 Thai floods so clearly that listeners perceive the living and sufferings of the victims. At the same time they could create hope and encouragement for them to fight through the crisis.